Differences in Emotional Intelligence, Learning Styles, Learning Motivation and Biology Learning Outcames of Male and Famale Students of Sman 4 Toraja Utara - Vilya Biring Pongbala; Nurhayati B; Hartati (BIOEDUKASI: Jurnal Biologi dan Pembelajarannya, 2025)
This study is an ex-post-facto study that aims to examine the differences in emotional intelligence, learning styles, learning motivation, and learning outcomes of male and female students of SMAN 4 Toraja Utara. Emotional Intelligence is a student's ability to recognize their own feelings and those of others, manage emotions effectively, and communicate effectively with others. Learning style is the way students absorb, organize, and process the information or learning materials they receive. Learning motivation is the drive that arises within students that drives and directs their learning behavior Emotional Intelligence, learning style and learning motivation  was measured by researchers using a Likert-scale questionnaire during the study. Biology learning outcomes are students' cognitive scores cognitive scores are obtained from scores after answering mid-semester multiple-choice questions developed and distributed by researchers covering the second half of the 2020/2021 academic year. This study aims to determine the differences between emotional intelligence, learning styles, learning motivation, and Biology learning outcomes of male and female science students at SMAN 4 Toraja Utara. Sampling was conducted using a stratified random sampling technique, resulting in a sample of 100 female students and 79 male students. This sample was obtained by calculating the total number of students and then determining the number of male and female representatives in each class.. Data collection techniques used instruments in the form of learning outcomes and questionnaires. The data analysis technique used is inferential statistical analysis. The results showed that (i) there were differences between emotional intelligence, learning styles, learning motivation, and learning outcomes for male and female students of SMAN 4 Toraja Utara.